New classification of analytic functions with negative coefficients - Shigeyoshi Owa; Milutin Obradovic (International Journal of Mathematics and Mathematical Sciences)
New classification of analytic functions with negative coefficients is given by using the coefficients inequality, that is, new subclass A(p,n,Bk) of analytic functions with negative coefficient is defined. The object of the present paper is to prove various distortion theorems for functions in A(p,n,Bk), and for fractional calculus of functions belonging to A(p,n,Bk). Further, some properties of the class A(p,n,Bk) are shown.